DEVELOPMENT OF POWERPOINT-BASED LEARNING MEDIA ON THE MATERIAL OF SYSTEM OF TWO VARIABLE LINEAR EQUATIONS - MASHITA NO'E, NURSHIAH RAMONA; Salajang, Santje; Anggriani, Nita (SOSCIED, 2025)
The lack of utilization of teaching materials that can attract students' attention is one of the problems in mathematics education that has been identified from various sources. The aim of this study is to create a valid, practical, and effective learning resource based on PowerPoint for eighth-grade students at MTs Nurul Yaqin Tondano. This study is a research and development (R&D) type that uses the 4-D development approach (Define, Design, Develop, and Disseminate). Evaluation by expert validators resulted in a very valid score of 91.33. Based on the responses from teachers and students, the practicality scores were 98 and 87.93, respectively, and were classified as very good. With a classical graduation rate of 81%, the created PowerPoint has met the effective criteria. In summary, the created PowerPoint is valid, practical, and effective for learning.